2009
DOI: 10.1631/jzus.b0920199
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of Litsea elliptica Blume essential oil on red blood cells of Sprague-Dawley rats

Abstract: Litsea elliptica Blume leaves have been traditionally used as medicinal herbs because of its antimutagenicity, chemopreventative and insecticidal properties. In this study, the toxic effects of L. elliptica essential oil against Sprague-Dawley rat's red blood cells (RBCs) were evaluated. L. elliptica essential oil was given by oral gavage 5 times per week for 3 treated groups in the doses of 125, 250, and 500 mg/(kg body weight), respectively, and the control group received distilled water. Full blood count, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…Additionally, TZ declined Hb%, RBCs count and HCT% significantly as in previous studies 54,55 . These changes may be due to the prevention of red blood cell synthesis via inhibition of erythropoisis in the bone marrow 56 as well as increase fragility and progressive destruction of RBCs due to binding of free radicals produced by TZ 57 .…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, TZ declined Hb%, RBCs count and HCT% significantly as in previous studies 54,55 . These changes may be due to the prevention of red blood cell synthesis via inhibition of erythropoisis in the bone marrow 56 as well as increase fragility and progressive destruction of RBCs due to binding of free radicals produced by TZ 57 .…”
Section: Discussionsupporting
confidence: 81%
“…Litsea elliptica Blume is a species within the Lauraceae family that can be widely found in the South East Asian forests ( Wong et al, 2014 , Taib et al, 2009 , Goh et al, 2017 ). The leaf of this tropical tree has been remarked for its ability to treat and prevent ailments such as stomach ulcers, cancer, fever and headaches by the local communities of Brunei Darussalam, Indonesia and Thailand ( Taib et al, 2009 , Goh et al, 2017 , Grosvenor et al, 1995 , Suksamerkun et al, 2013 , Bhamarapravati et al, 2002 ). In these regions, locals respectively have referred to the plant as “Pawas”, “Madang Perawas” and “Tham-mung”.…”
Section: Introductionmentioning
confidence: 99%
“…It also transports the metabolic waste products to the kidneys and liver to filter and excrete. Low RBCs are usually associated with anemia [32]. Adedapo et al [33] found that using crude aqueous extracts of Euphorbia over a period of 14 d of oral feeding led to low RBCs (anemia) in albino rats.…”
Section: Discussionmentioning
confidence: 99%